High-reliability high-thermal-conductivity wave-absorbing material and preparation method thereof
By optimizing the elemental composition of the wave absorbing powder and using a modifier to surface modify the heat conducting powder, the problem of the heat-conducting wave absorbing material being prone to cracking and powdering after aging at high temperature is solved, the material's aging resistance and reliability are improved, and high thermal conductivity and high wave absorbing properties are maintained.
Patent Information
- Application Number
- CN202411725706.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
Existing high-wattage thermally absorbing materials are prone to cracking and powdering after aging at high temperatures, resulting in attenuation of the thermal performance and EMC performance of the device. Common oxidation resistance methods will affect the electrical performance and aging stability of the material.
By optimizing the elemental composition of the absorbing powder, adding chromium and silicon elements to improve oxidation resistance, and using a modifier to surface modification of the absorbing powder and thermally conductive powder to enhance the interface compatibility between the powder and the resin.
It significantly improves the overall aging resistance of the thermally conductive and wave-absorbing material, delays the separation of the interface between the powder and the resin, enhances the reliability of the material, and maintains high thermal conductivity and high wave-absorbing properties.
Smart Images

Figure BDA0005159148510000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal interface materials, and in particular relates to a high-reliability high-heat-conductivity wave-absorbing material and a preparation method thereof. Background Art
[0002] Thermal interface materials are usually used between heat source chips and heat sources to conduct heat. During operation, they experience multiple high and low temperature cycles, humidity, temperature gradient changes, etc., which put forward higher requirements for reliability. As a type of thermal interface material, thermal conductive absorbing materials not only play a role in thermal performance, but also have the function of eliminating electromagnetic interference. Their reliability not only affects the thermal performance of the device, but also affects the device's signal processing level. At present, high-wattage thermal conductive absorbing materials are prone to cracking and powdering after aging at double 85 and high temperature 125℃ due to their high filler content, resulting in significant attenuation of the device's thermal gain and EMC gain. The hardness may even increase significantly after aging, causing serious impact of device cracking.
[0003] Different from pure thermal conductive materials, the reliability of thermal conductive absorbing materials is not only related to the resin, but also the aging resistance of the absorbing powder is another major factor affecting its performance. Conventional absorbing powder is carbonyl iron powder, which is easily oxidized in high humidity and high temperature environment, causing the interface state with the resin system to deteriorate significantly, affecting its reliability. The commonly used oxidation resistance method is to make a coating layer on its surface. On the one hand, the existence of the coating layer will cause a decrease in electrical properties; on the other hand, when the density is insufficient, it will reduce the material's resistance to double 85 aging. Therefore, it is of great significance to design and develop high-reliability thermal conductive absorbing materials. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a high-reliability and high-thermal-conductivity wave-absorbing material and a preparation method thereof. The specific technical scheme is as follows:
[0005] The first object of the present invention is to provide a method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material, comprising the following steps:
[0006] (1) modifying the absorbing powder with a modifier to obtain surface-modified absorbing powder; the absorbing powder comprises iron, chromium, and silicon, wherein the mass content of chromium is greater than 10%;
[0007] (2) modifying the thermal conductive powder with a modifier to obtain a surface-modified thermal conductive powder;
[0008] (3) Surface modified absorbing powder, surface modified thermal conductive powder, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst, and an inhibitor are mixed, and a high-reliability thermal conductive absorbing material is obtained after calendering and high-temperature baking.
[0009] The present invention optimizes the elemental composition of the absorbing material and fundamentally solves the oxidation resistance problem of the absorbing powder by adding chromium and silicon elements, thereby improving the corrosion resistance and oxidation resistance, thereby improving the overall aging resistance of the thermal conductive absorbing material; wherein the addition of silicon and other elements enables the thermal conductive absorbing material to form a solid solution, which not only improves the intrinsic aging resistance of the material from the source composition, but also avoids the secondary instability effect introduced by the coating layer on the basis of maintaining the absorbing performance; the present invention also performs modification treatment on the thermal conductive powder and the absorbing powder, greatly improving the interface compatibility between the powder and the resin, and further enhancing the thermal conductive and absorbing performance.
[0010] Furthermore, the absorbing powder also contains other elements such as copper and nickel.
[0011] It is beneficial to form a solid solution with silicon element in the thermal conductive absorbing material, improve the intrinsic aging resistance of the material from the source composition, and avoid the secondary instability effect introduced by the coating layer while maintaining the absorbing performance.
[0012] Furthermore, the particle size of the absorbing powder is 2-10 μm, preferably 2-5 μm.
[0013] Furthermore, the synthesis of the absorbing powder comprises the following steps:
[0014] 1) Select high-purity metal raw materials and put them into a vacuum melting furnace according to the element ratio to obtain alloy ingots;
[0015] 2) The alloy ingot is ball-milled to obtain alloy raw powder, and the alloy raw powder is sieved at multiple levels to obtain alloy raw powder with different particle size distributions;
[0016] 3) The alloy raw powder is sintered in a high-temperature sintering furnace with an external magnetic field, and after sintering in stages, the temperature is cooled to room temperature to obtain the microwave absorbing powder.
[0017] Furthermore, the purity of the metal raw material is greater than 95%, preferably greater than 99%, and more preferably greater than 99.9%.
[0018] Furthermore, the mass ratio of iron, chromium and silicon elements in the metal raw material is (69-89):(10-20):(1-5), and preferably the mass ratio of iron, chromium and silicon elements is (79-85):(10-15):(1-3).
[0019] Furthermore, in the step (1), the temperature of the vacuum melting furnace is 1500-2000° C., and the melting time is 5-25 min.
[0020] Furthermore, in the step (2), the ball milling time is 2-24 hours, the ball-to-material ratio is (10-40):1, preferably (20-30):1, and the ball mill is evacuated and filled with inert gas for protection during ball milling.
[0021] Furthermore, in the step (2), the multi-stage screening includes 300 mesh, 500 mesh, and 1500 mesh in increasing order; through the multi-stage screening, the required particle size is gradually obtained, and finally the powder is obtained with different particle size distributions, so the same batch of alloy raw powder is used for each grade.
[0022] Furthermore, in the step (3), the segmented sintering includes low-temperature segment sintering and high-temperature segment sintering, the temperature of the low-temperature segment sintering is 200-500°C, and the time is 8-20h; the temperature of the high-temperature segment sintering is 500-1000°C, and the time is 8-20h; the heating rate of the low-temperature segment sintering is 10-50°C / min, and the heating rate of the high-temperature segment sintering is 50-120°C / min; the gas atmosphere is nitrogen or hydrogen; the cooling rate is 100-200°C / min; and the external magnetic field is 5-50THz.
[0023] Furthermore, the thermally conductive powder is one or more of aluminum oxide, zinc oxide, aluminum nitride, and boron nitride.
[0024] Furthermore, the modifier is a composite of one or more of dodecyltrimethoxysilane, octyltrimethoxysilane, octadecyltrimethoxysilane, hexadecyltrimethoxysilane and dodecyltrimethoxysilane.
[0025] Furthermore, the modification treatment method is carried out in an atomizer with a dual channel, wherein a mixture of a modifier and vinyl silicone oil is sprayed out through one channel, and at the same time, absorbing powder or thermal conductive powder is sprayed out through another channel, and the two substances sprayed out through the dual channels are mixed to obtain surface-modified absorbing powder or surface-modified thermal conductive powder; the mass ratio of the modifier, vinyl silicone oil, absorbing powder or thermal conductive powder is (0.1-20):(1-10):(70-99).
[0026] Furthermore, the vinyl silicone oil includes one or more of single-end vinyl silicone oil, double-end vinyl silicone oil and mixed vinyl silicone oil, with a viscosity of 500-10000 mPa.s.
[0027] Furthermore, the hydrogen-containing silicone oil includes one or more of end hydrogen-containing silicone oil, side hydrogen-containing silicone oil and mixed hydrogen-containing silicone oil, and has a viscosity of 50-1000 mPa.s.
[0028] Furthermore, the catalyst is a platinum catalyst, the inhibitor is ethynyl cyclohexanol, the mass of the catalyst accounts for 0.1-0.3% of the total mass, and the mass of the inhibitor accounts for 0.05-0.2% of the total mass.
[0029] The second object of the present invention is to provide a high-reliability high-thermal-conductivity wave-absorbing material, which is prepared by the above-mentioned method for preparing the high-reliability high-thermal-conductivity wave-absorbing material.
[0030] The beneficial effects of the present invention are:
[0031] The present invention changes the composition of the absorbing powder material by synthesizing the absorbing powder, fundamentally solves the problem of oxidation resistance of the absorbing powder, enhances corrosion resistance and oxidation resistance, and improves the overall aging resistance of the thermal conductive absorbing material; adopts an atomization process to perform surface modification treatment and particle size control on the absorbing powder and the thermal conductive powder respectively, thereby achieving a maximum filling amount and improving the compatibility of the powder with the resin; its good interface compatibility delays the separation of the powder and the resin interface during the aging process, further enhances the reliability of the high thermal conductive absorbing material, and achieves the dual functional characteristics of high thermal conductivity and high absorption; the resin is selected to be a combination of high and low viscosity, with high viscosity being the main one, to improve the aging stability of the resin. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] Embodiment 1:
[0034] A preparation method of a high-reliability and high-thermal-conductivity wave-absorbing material comprises the following steps:
[0035] 1. Synthesis of High Reliability Absorbing Powder
[0036] (1) Selecting iron, chromium, silicon and copper metal ingots with a purity of 99.9%, and putting them into a vacuum melting furnace in a mass ratio of 87:11:2:0.5, the temperature of the vacuum melting furnace is 1500° C., and the alloy ingots are obtained by melting for 10 minutes;
[0037] (2) At a ball-to-material ratio of 20:1, the alloy ingot was ball-milled for 18 h, and alloy raw powders with different particle size distributions were obtained after sieving through 300 mesh, 500 mesh, and 1500 mesh in increasing order;
[0038] (3) The alloy raw powder undergoes two stages of high-temperature sintering. The sintering furnace is placed in a 50 THz magnetic field. The low-temperature stage sintering temperature is 500°C for 8 hours. The high-temperature stage sintering temperature is 1000°C for 8 hours. The low-temperature stage heating rate is 50°C / min, and the high-temperature stage heating rate is 120°C / min. The gas atmosphere is nitrogen. After sintering, the temperature is cooled to room temperature at a cooling rate of 200°C / min. The particle size of the high-reliability absorbing powder obtained after sintering is 5-10 microns.
[0039] 2. Preparation of high reliability and high thermal conductivity absorbing materials
[0040] (1) Using a wet method to combine the modifier with the absorbing powder to obtain a surface-modified absorbing powder
[0041] In a dual-channel atomizer, channel one sprays a mixture of a modifier dodecyltrimethoxysilane and a 500mpa.s double-terminated vinyl silicone oil in a mass ratio of 1:10 at a pressure of 2MPa, and channel two sprays high-reliability absorbing powder at a pressure of 2MPa, and the nozzle size is controlled to be 0.1mm; the mass ratio of the modifier dodecyltrimethoxysilane, vinyl silicone oil, and absorbing powder is 1:10:89, and the two substances sprayed through the dual channels are mixed to obtain surface-modified absorbing powder.
[0042] (2) Combine the modifier and thermal conductive powder by wet method to obtain surface modified thermal conductive powder
[0043] In a dual-channel atomizer, channel one sprays a mixture of modifier dodecyltrimethoxysilane and vinyl silicone oil in a mass ratio of 1:10 at a pressure of 2MPa, and channel two sprays 50μm aluminum nitride at a pressure of 2MPa, and the nozzle size is controlled to be 0.2mm; the mass ratio of the modifier dodecyltrimethoxysilane, vinyl silicone oil, and thermal conductive powder aluminum nitride is 1:8:91, and the two substances sprayed through the dual channels are mixed to obtain surface-modified aluminum nitride.
[0044] (3) 5 micron alumina, 20 micron alumina, 90 micron alumina, and surface modified aluminum nitride are mixed in a mass ratio of 0.5:4:4:1.5 to obtain a thermal conductive powder mixture, and then the thermal conductive powder mixture, surface modified absorbing powder, 1000 mPa.s double-terminated vinyl silicone oil, and 500 mPa.s end-hydrogen silicone oil D-500 are mixed in a mass ratio of 50:45:4:1, and then 0.2% of the total mass of platinum catalyst and 0.1% of the total mass of inhibitor ethynyl cyclohexanol are added. After mixing, the mixture is rolled and baked at 125°C for 30 minutes to obtain a high-reliability thermal conductive absorbing material.
[0045] Example 2
[0046] A preparation method of a high-reliability and high-thermal-conductivity wave-absorbing material comprises the following steps:
[0047] 1. Synthesis of high reliability absorbing powder
[0048] (1) Selecting iron and chromium metal ingots with a purity of 99.9%, and putting them into a vacuum melting furnace in a mass ratio of 87:13, the vacuum melting furnace temperature is 1500° C., and the melting time is 10 min to obtain an alloy ingot;
[0049] (2) At a ball-to-material ratio of 20:1, the alloy ingot was ball-milled for 18 h, and then sieved through 300 mesh, 500 mesh, and 1500 mesh in increasing order to obtain alloy raw powder with more uniform size distribution;
[0050] (3) The alloy raw powder undergoes two stages of high-temperature sintering. The sintering furnace is placed in a 50 THz magnetic field. The low-temperature stage sintering temperature is 500°C for 8 hours; the high-temperature stage sintering temperature is 1000°C for 8 hours. The heating rate in the low-temperature stage is 50°C / min, and the heating rate in the high-temperature stage is 120°C / min. The gas atmosphere is nitrogen. After sintering, the temperature is cooled to room temperature at a cooling rate of 200°C / min. The particle size of the high-reliability absorbing powder obtained after sintering is 3-8 microns.
[0051] Compared with Example 1, only the composition of the high reliability absorbing powder in the synthesis of the high reliability absorbing powder is different, and the remaining steps are the same as those in Example 1, which will not be repeated here.
[0052] Example 3
[0053] A preparation method of a high-reliability and high-thermal-conductivity wave-absorbing material comprises the following steps:
[0054] 1. Synthesis of High Reliability Absorbing Powder
[0055] The same as Example 1, no further details are given here.
[0056] 2. Preparation of high reliability and high thermal conductivity absorbing materials
[0057] (1) Using a wet method to combine the modifier with the absorbing powder to obtain a surface-modified absorbing powder
[0058] In the dual-channel atomizer, channel one sprays a mixture of a modifier hexadecyltrimethoxysilane and a 500mpa.s double-terminated vinyl silicone oil in a mass ratio of 1:10 at a pressure of 2MPa, and channel two sprays a high-reliability absorber at a pressure of 2MPa, and the nozzle size is controlled to be 0.1mm; the mass ratio of the modifier hexadecyltrimethoxysilane, vinyl silicone oil, and absorbing powder is 1:10:89, and the two substances sprayed through the dual channels are mixed to obtain surface-modified absorbing powder.
[0059] Steps (2) and (3) are the same as those in Example 1 and will not be repeated here.
[0060] Example 4
[0061] A preparation method of a high-reliability and high-thermal-conductivity wave-absorbing material comprises the following steps:
[0062] 1. Synthesis of High Reliability Absorbing Powder
[0063] The same as Example 1, no further details are given here.
[0064] 2. Preparation of high reliability and high thermal conductivity absorbing materials
[0065] (1) Using a wet method to combine the modifier with the absorbing powder to obtain a surface-modified absorbing powder
[0066] The same as Example 1, no further details are given here.
[0067] (2) Combine the modifier and thermal conductive powder by wet method to obtain surface modified thermal conductive powder
[0068] In a dual-channel atomizer, channel one sprays a mixture of a modifier dodecyltrimethoxysilane and a 500mpa.s double-terminated vinyl silicone oil in a ratio of 1:10 at a pressure of 2MPa, and channel two sprays 50μm boron nitride at a pressure of 2MPa, and the nozzle size is controlled to be 0.2mm; the mass ratio of the modifier dodecyltrimethoxysilane, vinyl silicone oil, and thermal conductive powder boron nitride is 1:8:91, and the two substances sprayed through the dual channels are mixed to obtain surface-modified boron nitride.
[0069] In step (3), the surface-modified aluminum nitride is replaced by surface-modified boron nitride. The rest is the same as in Example 1 and will not be described again.
[0070] Comparative Example 1
[0071] A preparation method of a high-reliability thermal conductive wave absorbing material comprises the following steps:
[0072] 1. Synthesis of High Reliability Absorbing Powder
[0073] (1) An iron metal ingot with a purity of 99.9% is selected and put into a vacuum melting furnace at a temperature of 1500° C. for a melting time of 10 min to obtain an alloy ingot;
[0074] (2) At a ball-to-material ratio of 20:1, the alloy ingot was ball-milled for 18 h, and the raw alloy powder was obtained after being sieved in increasing order through 300 mesh, 500 mesh, and 1500 mesh;
[0075] (3) The alloy raw powder undergoes two stages of high-temperature sintering. The sintering furnace is placed in a 50 THz magnetic field. The sintering temperature in the low-temperature stage is 500°C for 8 hours. The sintering temperature in the high-temperature stage is 1000°C for 8 hours. The heating rate in the low-temperature stage is 50°C / min, and the heating rate in the high-temperature stage is 120°C / min. The gas atmosphere is nitrogen. After sintering, the temperature is cooled to room temperature at a cooling rate of 200°C / min. The particle size of the high-reliability absorbing powder obtained after sintering is 5-10 microns.
[0076] 2. Preparation of High Reliability Thermally Conductive and Wave Absorbing Materials
[0077] The same as Example 1, no further details are given here.
[0078] Comparative Example 2
[0079] 1. Synthesis of high reliability absorbing powder
[0080] The same as Example 1, no further details are given here.
[0081] 2. Preparation of high reliability and high thermal conductivity absorbing materials
[0082] 5 micron alumina, 20 micron alumina, 90 micron alumina, and 90 micron aluminum nitride are mixed in a mass ratio of 0.5:4:4:1.5 to obtain a thermal conductive powder mixture, and then the thermal conductive mixture, high reliability absorbing powder, 1000 MPa.s double-ended vinyl silicone oil, and 500 MPa.s side hydrogen are mixed in a mass ratio of 50:45:4:1, and then 0.2% of the total mass of a platinum catalyst and 0.1% of the total mass of an inhibitor ethynyl cyclohexanol are added. After mixing, the mixture is rolled and baked at 125°C for 30 minutes to obtain a high reliability thermal conductive absorbing material.
[0083] Compared with Example 1, the surface modification process of the high-reliability absorbing powder and the thermal conductive powder is removed.
[0084] Comparative Example 3
[0085] A preparation method of a high-reliability and high-thermal-conductivity wave-absorbing material comprises the following steps:
[0086] 1. Synthesis of high reliability absorbing powder
[0087] (1) Selecting iron, chromium and silicon metal ingots with a purity of 99.9%, and putting them into a vacuum melting furnace in a mass ratio of 87:11:2, the temperature of the vacuum melting furnace is 1500° C., and the alloy ingots are obtained by melting for 10 minutes;
[0088] (2) The alloy ingot was ball-milled for 18 h at a ball-to-material ratio of 20:1, and the raw alloy powder was obtained after being sieved in increasing order through 300 mesh, 500 mesh, and 1500 mesh;
[0089] (3) The alloy raw powder is subjected to two stages of high-temperature sintering, the low-temperature stage sintering temperature is 500°C, the time is 8 hours; the high-temperature stage sintering temperature is 1000°C, the time is 8 hours; the low-temperature stage heating rate is 50°C / min, and the high-temperature stage heating rate is 120°C / min; the gas atmosphere is nitrogen; after sintering, the temperature is cooled to room temperature at a cooling rate of 200°C / min; the high-reliability absorbing powder obtained after sintering has a particle size of 5-10 microns.
[0090] Compared with Example 1, the magnetic field environment of the high-temperature sintering furnace is removed.
[0091] 2. Preparation of High Reliability Thermally Conductive and Wave Absorbing Materials
[0092] The same as Example 1, no further details are given here.
[0093] Test Results
[0094] The thermal conductive absorbing materials prepared in Examples 1-4 and Comparative Examples 1-3 were tested for performance. The thermal conductivity was tested using D5470, the hardness was tested using a Shore durometer, and the absorbing performance was tested using GJB 2038A-2011 "Test Method for Reflectivity of Radar Absorbing Materials". The test results are shown in Table 1:
[0095] Table 1. Test results of thermal conductive and wave absorbing materials performance of embodiments and comparative examples
[0096]
[0097] It can be seen from the data in Table 1 that the addition of chromium and silicon elements fundamentally improves the oxidation resistance of the absorber and further improves the reliability of the thermal conductive absorbing material; the modification process of the absorbing powder and thermal conductive powder is beneficial to the improvement of thermal conductivity and the reduction of initial hardness. At the same time, it also has a significant improvement effect on aging reliability, which is an indispensable step to obtain high-reliability thermal conductive absorbing materials; the magnetic field environment of the sintering furnace during the preparation of the absorbing powder is beneficial to the improvement of the magnetic properties of the absorbing material, thereby improving its absorbing performance. The three key formula compositions and process steps mentioned above are the core elements for the preparation of high-reliability and high-thermal conductive absorbing materials. They not only fundamentally solve the oxidation resistance problem of thermal conductive absorbing materials, but also take into account high thermal conductivity and high absorption. At the same time, the hardness improvement is significantly reduced after reliability testing.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material, characterized in that: The steps include: (1) modifying the absorbing powder with a modifier to obtain surface-modified absorbing powder; the absorbing powder comprises iron, chromium, and silicon, wherein the mass content of chromium is greater than 10%; (2) modifying the thermal conductive powder with a modifier to obtain a surface-modified thermal conductive powder; (3) Surface modified absorbing powder, surface modified thermal conductive powder, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst, and an inhibitor are mixed, and a high-reliability thermal conductive absorbing material is obtained after calendering and high-temperature baking.
2. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 1, characterized in that: The synthesis of the absorbing powder comprises the following steps: 1) Select high-purity metal raw materials and put them into a vacuum melting furnace according to the element ratio to obtain alloy ingots; 2) The alloy ingot is ball-milled to obtain alloy raw powder, and the alloy raw powder is sieved at multiple levels to obtain alloy raw powder with different particle size distributions; 3) The alloy raw powder is sintered in a high-temperature sintering furnace with an external magnetic field, and after sintering in stages, the temperature is cooled to room temperature to obtain the microwave absorbing powder.
3. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 2, characterized in that: The mass ratio of iron, chromium and silicon elements in the metal raw material is (69-89):(10-20):(1-5).
4. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 1, characterized in that: The thermally conductive powder is one or more of aluminum oxide, zinc oxide, aluminum nitride, and boron nitride.
5. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 1, characterized in that: The modifier is a composite of one or more of dodecyltrimethoxysilane, octyltrimethoxysilane, octadecyltrimethoxysilane, hexadecyltrimethoxysilane and dodecyltrimethoxysilane.
6. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 1, characterized in that: The modification treatment method is carried out in an atomizer with two channels, wherein a mixture of a modifier and vinyl silicone oil is sprayed out through one channel, and at the same time, absorbing powder or thermal conductive powder is sprayed out through another channel, and the two substances sprayed out through the two channels are mixed to obtain surface-modified absorbing powder or surface-modified thermal conductive powder; the mass ratio of the modifier, vinyl silicone oil, absorbing powder or thermal conductive powder is (0.1-20):(1-10):(70-99).
7. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to any one of claims 1 to 6, characterized in that: The vinyl silicone oil includes one or more of single-end vinyl silicone oil, double-end vinyl silicone oil and mixed vinyl silicone oil, with a viscosity of 500-10000mPa.s; the hydrogen-containing silicone oil includes one or more of end hydrogen-containing silicone oil, side hydrogen-containing silicone oil and mixed hydrogen-containing silicone oil, with a viscosity of 50-1000mPa.s.
8. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 2, characterized in that: In the step (1), the temperature of the vacuum melting furnace is 1500-2000° C., and the melting time is 5-25 min.
9. The method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to claim 2, characterized in that: In the step (3), the segmented sintering includes low-temperature segment sintering and high-temperature segment sintering, the low-temperature segment sintering temperature is 200-500°C, the time is 8-20h; the high-temperature segment sintering temperature is 500-1000°C, the time is 8-20h; The heating rate of sintering in the low temperature stage is 10-50°C / min, and the heating rate of sintering in the high temperature stage is 50-120°C / min; the gas atmosphere is nitrogen or hydrogen; the cooling rate is 100-200°C / min; and the external magnetic field is 5-50THz.
10. A high reliability and high thermal conductivity wave absorbing material, characterized in that: The material is prepared by the method for preparing a high-reliability and high-thermal-conductivity wave-absorbing material according to any one of claims 1 to 9.